TWELVE-WEEK MULTICENTER OPEN-LABEL RANDOMIZED COMPARATIVE STUDY OF THE EFFICACY AND SAFETY OF METHOTREXATE AS A CONCENTRATED SOLUTION FOR SUBCUTANEOUS ADMINISTRATION AND AS 15-MG TABLETS PER WEEK FOR RHEUMATOID ARTHRITIS - Yu. V. Muravyev; V. I. Mazurov; E. L. Nasonov (Научно-практическая ревматология)
Objective: to evaluate of the efficacy of methotrexate (MTX) as a concentrated solution (50 mg/ml) for subcutaneous administration versus coated tablets at equal oral doses of 15 mg/week for rheumatoid arthritis (RA).Subjects and methods. The study was conducted at two centers: the V.A. Nasonova Research Institute of Rheumatology and the Saint Petersburg Medical Academy of Postgraduate Education, Federal Agency for Healthcare and Social Development. At each center, the patients were randomized into two groups: a study group and a control group. In the study group, MTX was used as a concentrated solution (50 mg/ml) for subcutaneous administration at a dose of 15 mg/week. The controls were patients with RA who took MTX as coated tablets once weekly at the same dose as used in the study group. A trend in the 28-joint disease activity score (DAS28) was a main criterion for evaluating therapy efficiency. For efficiency evaluation, other criteria were additionally used; these included disease activity assessment by a physician; functional status assessment (Health Assessment Questionnaire); C-reactive protein level. The safety of the used MTX formulations was evaluated during each visit: the patients' subjective sensations and examination and laboratory findings were kept in mind.Results and discussion. After randomization (totally at the two centers), the study group included 42 patients and the control group comprised 23. Based on 95% confidence interval for the mean, it may be concluded that the efficiency of MTX as a solution for subcutaneous administration (the study group) is no less than that of MTX as tablets (the control group). Subcutaneous MTX was shown to be associated with the lower rate of therapy correction than oral MTX; and did not differ from it in toxicity. In addition, subcutaneous MTX may noticeably reduce the need for biological agents.The final DAS28 value in the study group does not exceed that in the control group (t-test). Remission was observed only after subcutaneous administration of the drug.Conclusion. Based on the findings, it can be concluded that MTX as a concentrated (50 mg/ml) solution for subcutaneous administration may be the drug of choice for the treatment of patients with active RA.